The implication of the PD-1/PD-L1 checkpoint in chronic periodontitis suggests novel therapeutic opportunities with natural products - Christian Bailly (Elsevier, 2020)
Summary: An analysis of the implication of the PD-1/PD-L1 immune checkpoint in periodontitis is provided with the objective to propose a novel therapeutic approach. An exhaustive survey of the literature has been performed to answer two questions: (1) Is there a role for PD-1 and/or PD-L1 in the development of periodontitis? (2) Which natural products interfere with the checkpoint activity and show activity against periodontitis? All online published information was collected and analyzed. The pathogenic bacteria Porphyromonas gingivalis, through its membrane-attached peptidoglycans, exploits the PD-1/PD-L1 checkpoint to evade immune response and to amplify the infection. Three anti-inflammatory natural products (and derivatives or plant extracts) active against periodontitis and able to interfere with the checkpoint were identified. Both curcumin and baicalin attenuate periodontitis and induce a down-regulation of PD-L1 in cells. The terpenoid saponin platycodin D inhibits the growth of P. gingivalis responsible for periodontitis and shows a rare capacity to induce the extracellular release of a soluble form of PD-L1, thereby restoring T cell activation. A potential PD-L1 shedding mechanism is discussed. The targeting of the PD-1/PD-L1 immune checkpoint could be considered a suitable approach to improve the treatment of chronic periodontitis. The plant natural products curcumin, baicalin and platycodin D should be further evaluated as PD-1/PD-L1 checkpoint modulators active against periodontitis.